Peran Brand Satisfaction dalam Memediasi Brand Experience dan Brand Trust terhadap Purchase Intention Produk “CC” - Tommy Setiawan Ruslim (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Health is an essential aspect that is crucial for every individual to engage in daily activities. With good health and physical fitness, the body has the strength to prevent various diseases. Maintaining health needs to start from oneself by adopting good habits for the body, namely by leading a healthy lifestyle. However, a healthy lifestyle is often overlooked by some people. Unhealthy lifestyles can lead to diabetes, which is the accumulation of excess sugar in the bloodstream. The increasing number of diabetes patients significantly results from unhealthy lifestyles, one of which is consuming high-sugar beverages such as soft drinks. The soft drink brand "CC" is the most popular packaged beverage brand among the public, which is also a contributing factor to diabetes. CC continues to receive high demand from consumers, which is in line with the high purchase intention of consumers. Purchase intention, which is the willingness of customers to purchase a particular product, can be influenced by brand satisfaction, meaning that brand satisfaction can encourage customers to buy products. Brand experience and brand trust can also affect brand satisfaction, where customers will feel more satisfied with a brand if they are increasingly influenced by positive experiences and customer trust can generate positive expectations for the brand. This study aims to determine the factors influencing the purchase intention of soda beverages "CC" by testing the variables of brand experience and brand trust on the purchase intention variable mediated by brand satisfaction.